THE DETERMINATION OF ACCEPTANCE OF THE CHARACTERISTICS AND THE INFLUENCE OF DAMAGE ON THE PERFORMANCE OF TANK CARS - Moikin, D. O. (Science and Transport Progress, 2005)
The paper presents the results of simulation of the strain-stress fields in the bottom of a tank-car with different damages. Aims of the further research are formulated.